MANAGEMENT OF ARABIC TEACHING AT ABDUL RAHMAN BIN AUF INSTITUTE, MUHAMMADIYAH MALANG UNIVERSITY / إدارة تعليم اللغة العربية في معهد عبد الرحمن بن عوف جامعة محمدية مالانج - Irmariyadi, Irmariyadi; Nabil, Moch Zidni; Arifa, Zakiyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Teaching Arabic in Indonesia continues to develop over time. This development can be seen through the establishment of institutes, schools, universities and institutions specialized in teaching Arabic. Therefore, to run and develop learning Arabic language requires good management. The objectives of this research are to describe the planning, implementation, and evaluation of the Department of Arabic Language Education at the Abdul Rahman Bin Auf Institute, Muhammadiyah Malang University. The methodology of this research is the qualitative approach in the case study method. Method of data collection through interviews, observation and documentation. Research topics were chosen using targeted sampling. The results of this research are that the Department of Arabic Language Teaching at Abdul Rahman bin Auf Malan Institute has been fulfilled, which consists of planning, organizing, implementing, and monitoring. From the planning, the researcher obtains: the educational curriculum, writing the teaching plan, teaching materials and student registration, and from the implementation: the teaching plan, the teaching method and the teaching aids, and from the evaluation side: the evaluation process, the test, the success criteria, and the evaluation at the end of the month.